Utilization of Drone Mapping (Photogrammetry) Application to Evaluate the Volume of Inundation Area at Margatiga Dam - Rizky Saputra; Umboro Lasminto (International Journal Labs, 2023)
In 2017 the planned volume of the Margatiga Dam inundation area at an elevation of +23,000 is 42,311,835.60 m3. Using the drone mapping method (photogrammetry) there is a difference in the volume of the puddle area at an elevation of +23,000 with a result of 41,005,959.97 m3. The method used to evaluate the volume of the inundation area at the Margatiga Dam is taking field data using drones in the form of aerial photography, testing the accuracy of GCP (Ground Control Point) geometry and calculating volume using Autodesk Civil 3D software. The volume was obtained after going through an accuracy test on the geometry of GCP alternative one with an accuracy test value of 0.723 meters and an RMSE value of 0.438. Processing using Agisoft software is processed into two parts, namely the first processing using alternative GCP geometry 1 and the second processing using alternative GCP geometry 2. The design of the planning consultant in 2017 regarding the reservoir volume at the Margatiga Dam at an elevation of +23,000 was 42,311,835.60 m3. By evaluating the volume of inundation using the photogrammetric method, a volume of 41,005,959.97 m3 was obtained with a selection of contour intervals of 0.75 meters.